Evaluasi Usability pada Website KPU Menggunakan Metode System Usability Scale - Rusmawan Abdullah Sani (Forum Kerjasama Pendidikan Tinggi (FKPT), 2026)
The digitalization of public services at the General Elections Commission (KPU) is vital for election transparency, yet technical obstacles such as slow loading times and navigation complexity are still frequently reported. This study aims to evaluate the usability of the kpu.go.id website using the System Usability Scale (SUS) method to measure user perception of satisfaction, effectiveness, and efficiency in a standardized manner. This study was conducted in Indonesia with 100 respondents who had previously accessed the kpu.go.id website, using accidental sampling. A quantitative descriptive approach was employed by distributing a questionnaire consisting of ten standard SUS statements. The results show a mean SUS score of 71.5. Based on evaluation parameters, this score places the KPU website in the